Using Virtual Manipulative Instruction to Teach the Concepts of Area and Perimeter to Secondary Students With Learning Disabilities - Satsangi, Rajiv; Bouck, Emily C. (Learning disability quarterly, 2015)
Secondary students with a learning disability in mathematics often struggle with the academic demands presented in advanced mathematics courses, such as algebra and geometry. With greater emphasis placed on problem solving and higher level thinking skills in these subject areas, students with a learning disability in mathematics often fail to keep pace with their general education peers. This study sought to address the lack of existing empirical research targeting viable interventions for learning the concepts of area and perimeter for secondary students with a learning disability in mathematics. Through the use of a multiple baseline design across three participants, virtual manipulatives were found to be an effective tool to acquire, maintain, and generalize the concepts of area and perimeter. Results from this study provide new evidence showing virtual manipulatives to be a viable and accessible technology to teach students with learning disabilities advanced mathematical concepts.